2017
DOI: 10.1037/mot0000051
|View full text |Cite
|
Sign up to set email alerts
|

What does it take for sour grapes to remain sour? Persistent effects of behavioral inhibition in go/no-go tasks on the evaluation of appetitive stimuli.

Abstract: Recent studies have provided contradictory results on whether the pairing of appetitive stimuli with no-go responses in go/no-go tasks leads to a devaluation of these stimuli. The authors of the present studies argue that devaluation effects after pairings of appetitive stimuli (e.g., unhealthy snacks or fruit) with no-go responses are usually short-lived but can become persistent if the stimuli form a meaningful category of appetitive stimuli that one should usually avoid (e.g., unhealthy snacks). In three st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…The visualization of liking data hinted at a general devaluation trend for all foods (figure 4), which has also been observed in previous studies (e.g. [27,33,75]). This could be attributed to the regression to the mean, but we advocate that the potential of over-exposure effects in ICT protocols that repeatedly present a limited number of energy-dense foods should be formally addressed in future research.…”
Section: Discussionsupporting
confidence: 83%
“…The visualization of liking data hinted at a general devaluation trend for all foods (figure 4), which has also been observed in previous studies (e.g. [27,33,75]). This could be attributed to the regression to the mean, but we advocate that the potential of over-exposure effects in ICT protocols that repeatedly present a limited number of energy-dense foods should be formally addressed in future research.…”
Section: Discussionsupporting
confidence: 83%
“…Only few studies have measured both the ERPs and food intake in the laboratory and it is thus difficult to say whether the absence of significant effects is due to our specific methods (Nijs et al, ). However, the N2 was not sensitive to calorie content of the foods which indicates that participants might not have created meaningful food categories (high‐ vs. low‐caloric foods), a prerequisite for persistent effects of training on stimulus evaluation (Serfas, Florack, Büttner, & Voegeding, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the N2 was not sensitive to calorie content of the foods which indicates that participants might not have created meaningful food categories (highvs. low-caloric foods), a prerequisite for persistent effects of training on stimulus evaluation (Serfas, Florack, Büttner, & Voegeding, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The present findings imply that such manipulation could have effects on preferences for perceived value of products. Because previous research has also shown that devaluation effects are sometimes, but not always shortlived (Serfas et al, 2017), we regard it as a fruitful approach for future research on consumer behavior to examine whether and under which circumstances effects of selective attention are enduring and can be applied in advertising.…”
Section: Discussionmentioning
confidence: 99%